Chokha Mela - Edited by Anant Pai; Fables; Humours (Mumbai; Amar Chitra Katha, 2022)
Chokha was a young boy when he first heard the call of the Lord. But all attempts to enter temples were thwarted by those who only saw him as a Mahar, an untouchable. However, Chokha's devotion was such that his heart became a temple and he sang with purity and complete faith. Chokha Mela's Abhangs or verses echo to this day around the temples of Maharashtra.